Systematic review of pharmacoeconomic models for schizophrenia. Issue 1 (1st January 2018) - Zhou, Junwen; Millier, Aurélie; Toumi, Mondher
ABSTRACT: Background : Economic models are broadly used in the economic evaluation of antipsychotics in schizophrenia. Our objective was to summarize the structure of these models. Methods : Model-based economic evaluations of antipsychotics in schizophrenia were identified through Medline and Embase. General information was extracted including analysis type, model type, perspective, population, comparator, outcome, and timeframe. Model-specific structures for decision tree (DT), cohort- and patient-level Markov model (CLMM, PLMM), and discrete-event simulation (DES) models were extracted. Results : A screen of 1870 records identified 79 studies. These were mostly cost-utility analyses (n = 48) with CLMM (n = 32) or DT models (n = 29). They mostly applied payer perspective (n = 68), focused on general schizophrenia for relapse prevention (n = 73), compared pharmacotherapies as first-line (n = 71), and evaluated incremental cost per quality-adjusted life year (QALY) gained (n = 40) with a 1-year (n = 32) or 5-year (n = 26) projection. DT models progressed with the branching points of response, relapse, discontinuation, and adherence. CLMM models transitioned between disease states, whereas PLMM models transitioned between adverse event states with/without disease state. DES models moved forward with times to remission, relapse, psychiatrist visit, and death. Conclusions : A pattern of pharmacoeconomic models for schizophrenia was identified. More subtle structures and patient-level models are suggested for a future modelling exercise.